Adapting the good behavior game for special education classrooms. Issue 5 (11th February 2021) - Groves, Emily A.; May, Richard J.; Rees, Rachel E.; Austin, Jennifer L.
Abstract: The good behavior game (GBG) is a classroom management intervention that employs a group contingency to support appropriate behavior and reduce classroom disruptions. To date, the majority of GBG research has included participants of typical development in mainstream education classrooms or alternative schools. The current study evaluated the GBG across two classrooms in a special education school in Wales. Children included those with both intellectual and physical disabilities. Although some adaptations were made to accommodate individual student needs, those adjustments were minimal and required little additional effort from teachers. Results were evaluated using a single‐case withdrawal design and indicated that the GBG was effective at reducing disruptive and off‐task behavior in both classrooms.